The Undiscovered Country - Ferguson, Russell; Philbin, Ann; the Hammer Museum, Los Angeles (Los Angeles : The Regents of the University of California, 2004)
Andersson, Mamma ; Baldessari, John ; Bryan, Edgar ; Celmins, Vija ; Doig, Peter ; Duwenhögger, Lukas ; Eastman, Mari ; Eggerer, Thomas ; Everberg, Kirsten ; Guston, Philip et al.
The Undiscovered Country, the Hammer Museum, Los Angeles, 3 oktober 2004-16 January 2005
kunstcatalogus